Assessment of HPV screening modalities within primary care: a systematic review - Waly, Yahya Mostafa; Sharafeldin, Abu-Baker; Al-Majmuei, Abdulrahman; Alatoom, Mohammad; Fredericks, Salim; Aloia, Adri-Anna (Frontiers in Medicine, 2025)
IntroductionMost cervical cancer precancerous lesions are associated with high-risk human papillomavirus (HPV) subtypes. Early detection through screening is crucial for preventing and managing HPV-related diseases. HPV Self-sample screening is a proposed method that can mitigate socioeconomic disparities, reduce embarrassment and costs of screening. This can possibly reduce the overall disease burden.MethodsA search strategy was conducted across multiple databases, including PubMed, Cochrane Library, Scopus, and Embase. Data extraction was performed using a standardized form to collect detailed information on study characteristics, participant demographics, and various outcomes. The quality and risk of bias in the articles were assessed using the Critical Appraisal skills programme (CASP) checklist, and the Cochrane Risk of Bias (ROB) tool.ResultsOur review consistently found that HPV self-sampling is comparable to clinician-collected samples in terms of HPV detection rates and sensitivity, supporting the idea that HPV self-sampling can be a viable alternative for cervical cancer screening. Across the studies, self-sampling showed comparable or greater effectiveness to clinician-collected samples in detecting HPV in individuals. Specificity was comparable between both methods, with clinician-collected sampling slightly outperforming HPV self-sampling in some cases. Moreover when analyzing the negative predictive value (NPV) and positive predictive value (PPV) across the studies, it was evident that there was little difference between clinician-collected sampling and HPV self-sampling. 64.3% favored self-sampling over clinician-collected sampling due to increased comfort and privacy. Overall, the evidence suggests that self-sampling is an effective, patient-preferred, and cost-efficient alternative to clinician-collected sampling, particularly in under-screened populations.